Upsurge in Firearm related Deaths among Children and Adolescents in the United States: An Alarming Trend - Bashar, MD. Abu; Sheikh, Nishat Ahmed (Indian Journal of Community Health, 2023)
Firearm-related violence is a leading cause of death, disproportionately affecting adolescents and young adults across the world, especially in the Americas. It is one of the most common forms of suicide and homicide across the globe. Recent data from the Centers for Disease Control and Prevention (CDC) shows an alarming increase in firearm-related mortality among children and Adolescents which is a cause of concern and requires strict gun licensing regulation in countries like the U.S.